The conquest of the Holy Land by Ṣalāḥ al-Dīn : a critical edition and translation of the anonymous Libellus de expugnatione Terrae Sanctae per Saladinum /: a critical edition and translation of the anonymous Libellus de expugnatione Terrae Sanctae per Saladinum. (2019) - Brewer, Keagan; Kane, James H
No abstract available